Carbonized Grain from Mortens Sande 2 : A Single Grave Site in Northwest Jutland - Robinson, David; Kempfner, Dorthe (Journal of Danish Archaeology, 1987)
Carbonized Grain from Mortens Sande 2 - A Single Grave Site in Northwest Jutland